An experimental switchable stiffness device for shock isolation - Ledezma-Ramirez, D. F.; Ferguson, N. S.; Brennan, M. J. [UNESP] (Academic Press Ltd Elsevier B.V. Ltd, 2012)
The development of an experimental switching stiffness device fcr shock isolation is presented. The system uses magnetic forces to exert a restoring force, which results in an effective stiffness that is used to isolate a payload. When the magnetic force is turned on and off, a switchable stiffness is obtained. Characterization of the physical properties of the device is presented. They are estimated in terms of the percentage stiffness change and effective damping ratio when switched between two constant stiffness states. Additionally, the setup is used to implement a control strategy to reduce the shock response and minimize residual vibration. The system was found to be very effective for shock isolation. The response is reduced by around 50 percent compared with passive isolation showing good correlation with theoretical predictions, and the effective damping ratio in the system following the shock was increased from about 4.5 percent to 13 percent. (c) 2012 Elsevier Ltd. All rights reserved.